Sericin and sericin-derived peptide alleviate viral pathogenesis in mice though inhibiting lactate production and facilitating antiviral response. (December 2021) - Li, Yongkui; Huang, Ying; Pan, Pan; Che, Xu; Zhang, Yaru; Zhang, Yeshun; Amal, Algahtany; Li, Xin; Niu, Wenjing; Luo, Nachuan; Zhang, Wen; Gao, Daolong; et al.
Highlights: Sericin alleviate pathogenesis of RNA viral infection in vivo . Sericin promotes RIG-I-MAVS signaling to boost IFN-dependent antiviral effect through attenuating glycolysis rate and repressing cellular lactate production. Sericin derived peptide F5-SP has the same antiviral function as sericin. Abstract: Sericin, a bioactive protein forming the outer layer of silk, promotes cell proliferation and cell adhesion, inhibits inflammation, and provides nutrition. Here, we obtain endotoxin-free sericin and explore its potential property in antiviral activity towards infectious diseases. In vesicular stomatitis virus (VSV) infection model, pre-treatment with sericin obviously inhibits VSV replication and reduces organ injury in infected mice. Further studies reveal that pre-incubating cells with sericin results in suppressing the infections of VSV and Enterovirus 71 (EV71) in infected cells. More evidences show that upon virus infection, the levels of interferons (IFNs) are significantly elevated in the cells pre-incubated with sericin as compared to untreated cells, indicating that sericin promotes virus-induced antiviral immune responses. Mechanistically, sericin attenuates cell glycolysis rate and reduces lactate production. Low level of lactate benefitting from sericin treatment facilitates the RIG-I-MAVS signaling pathway to initiate interferon activation. Notably, like sericin, a sericin-derived peptide F5-SP shares the same functions to exert antiviral activity both in vitro and in vivo . Therefore, we report that sericin and sericin-derived peptide F5-SP enhance antiviral innate immune response through inhibiting lactate production, which discovers a promising biomedical application of sericin in the prevention and treatment of viral infectious diseases. Graphical abstract: Image, graphical abstract